Piperine, a black pepper compound, induces autophagy and cellular senescence mediated by NF-κB and IL-6 in acute leukemia - Kantorn Charoensedtasin; Wasinee Kheansaard; Sittiruk Roytrakul; Dalina Tanyong (BMC, 2024)
Abstract Acute leukemia is characterized by abnormal white blood cell proliferation with rapid onset and severe complications. Natural compounds, which are alternative treatments, are widely used in cancer treatment. Piperine, an alkaloid compound from black pepper, exerts anticancer effects through the cell death signaling pathway. Autophagy and senescence signaling pathways are considered target signaling pathways for cancer treatment. In this study, we investigated the effects of piperine via autophagy and senescence signaling pathways in NB4 and MOLT-4 cells. The MTT assay results demonstrated that piperine significantly decreased the viability of NB4 and MOLT-4 cells. Piperine induced autophagy by increasing LC3, Beclin-1 and ULK1 and decreasing mTOR and NF-κB1 expression in NB4 and MOLT-4 cells. In addition, piperine increased senescence-associated beta-galactosidase fluorescence intensity by increasing p21 and IL-6 expression while decreasing CDK2 expression in NB4 and MOLT-4 cells. In conclusion, our study provides additional information about the induction of autophagy and senescence by piperine in acute leukemia.